2008
DOI: 10.30638/eemj.2008.001
|View full text |Cite
|
Sign up to set email alerts
|

"Waste Not, Want Not" a Study of Household Attitude Toward Recycling of Solid Wastes

Abstract: Solid waste management in Malaysia has become an increasingly important task of local government authorities over the recent years as a result of urban population growth, industrialization and an increase in quantity and variation in the types of waste generated. For this reason the government of Malaysia through the Ministry of Housing and Local Government has taken various measures to promote recycling amongst its population. However, a recycling program is only successful if households support and actively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…In fact, eco-literacy was a significant predictor of environmentally friendly behavior [42]. However, a few existing studies found no significant effect of the eco-literacy on enthusiasm to conserve the environment [43]. The inconsistent findings of prior studies call for further investigation.…”
Section: Eco-literacymentioning
confidence: 95%
“…In fact, eco-literacy was a significant predictor of environmentally friendly behavior [42]. However, a few existing studies found no significant effect of the eco-literacy on enthusiasm to conserve the environment [43]. The inconsistent findings of prior studies call for further investigation.…”
Section: Eco-literacymentioning
confidence: 95%
“…Ramayah et al, 2012). However, the few existing studies report no significant effect of a conceptual understanding of one's surrounding environment on their enthusiasm to conserve the environment (Omran and Gebril, 2011;Said et al, 2007). In a recent study on similar issues in Malaysia, it was highlighted that even individuals possessing high levels of environmental awareness failed to act and/or practice certain attitudes that could improve their surroundings (Hassan et al, 2010).…”
Section: Recycling Intentions and Behaviorsmentioning
confidence: 99%
“…Generally, solid waste management is given a very low priority in Nigeria and other sub-Sahara Africa. Solid waste management is given very low priority in the budget due to limited finances (Omran, and Read, 2007). As a result, very limited funds are provided to the solid waste management sector by the governments.…”
Section: Constraints To Solid Waste Management In Nigeriamentioning
confidence: 99%